ANALYSIS OF PROBLEMS SPECIFIC TO THE FIELD OF DRUG DEVELOPMENT BY INTERNATIONAL AND RUSSIAN MANUFACTURING COMPANIES - Tsypkina1, Anastasia; Rozhnova, Svetlana; Krylova, Olga; Mamontov, Elza; Tananakina, Galina; Yarkova, Natalia (Revista Inclusiones, 2020)
The article is devoted to the analysis of problems in the development of new medicines (drugs) typical for world and Russian manufacturers. It is established that Russian manufacturing organizations mostly focus both on the lack of approaches to the organization of the process and the lack of regulation documents at the national and local levels. On the contrary, regulators of the circulation system of medicines in many countries with developed economies have approved the documents regulating approaches to drug development which were designed taking into account the specifics of the organization of processes and international standards of good practices. In this regard, it is relevant to study the possibility and rationality of applying a systematic approach which allows a comprehensive study to the organization of new medicine developmental process at Russian pharmaceutical enterprises, as well as to the development of methodological support for the processes and procedures of drug development for Russian manufacturers.